The Relationship between Loin Surface Visual Characteristics with Instrumental Colour and Tenderness Characteristics from Five South African Beef Breeds - (:unkn) unknown (My University, 2021)
The study describes the relationship between visual and instrumental measurements for colour and tenderness between 5 South African beef breeds; Bos indicus (Brahman), Sanga type (Nguni), British Bos taurus (Angus), European Bos taurus (Charolais) and the composite (Bonsmara), 10 animals per genotype were used, n=50. The animals were finished off on a feedlot diet for a period of between 90-110 days at the ARC-AP feedlot and were slaughtered at the ARC-AP abattoir when they reached a live weight which would produce a carcass of Class A (no permanent incisors), and fat class 2 to 3 (1-5 mm) (South African Beef Classification System). After exsanguination, the carcasses were split and the right sides were electrically stimulated (ES) and the left sides were not stimulated (NS), but delay chilled. Steaks from both ES and NS treatments were aged until 3 days (d) post mortem (pm) on polystyrene plates at 6°C in a display cabinet and until 9, 14 and 20 d pm in vacuum bags at 1-4°C in a cold room. The steaks were then evaluated by visual analysis for colour, marbling, fibre separation, surface texture and structure integrity using a 10 member trained panel. Instrumental colour was measured using Minolta meter (CIE L*, a*, b*). Instrumental tenderness was measured by shear force using Instron.
Keywords: African Research